Surviving together: domestic violence and mother-child relationships - Katz, Emma (2015)
This thesis explores how mothers and children in the UK are affected by domestic violence, resist it, and actively support one another's recoveries. The focus extends beyond 'incidents' of physical violence, into the commonplace, the subtle and the everyday. This thesis shows that supportive mother-child relationships may enhance the well-being and recoveries of both mothers and children. It highlights the need to expand professional supports that repair and strengthen mother-child relationships.